Partial Substitution of Organic Fertilizer with Chemical Fertilizer Improves Soil Biochemical Attributes, Rice Yields and Restores Bacterial Community Diversity in a Paddy Field - Iqbal, Anas; He, Liang; Ali, Izhar; Yuan, Pengli; Khan, Abdullah; Hua, Zhang; Wei, Shanqing; Jiang, Ligeng (Frontiers in Plant Science, 2022)
Conventional farming systems are highly reliant on chemical fertilizers (CFs), which adversely affect soil quality, crop production and the environment. One of the major current challenges of current agriculture is finding ways to increase soil health and crop yield sustainably. Manure application as a substitute for CF is an alternative fertilization strategy for maintaining soil health and biodiversity. However, little is known about the complex response of soil bacterial communities and soil nutrients to manure and CFs application. This study reports the response of soil nutrients, rice yield, and soil microbial community structure to two years of continuous manure and CFs application. The study consisted of six treatments: no N fertilizer control (Neg-Con); 100% chemical fertilizer (Pos-Con); 60% cattle manure (CM) + 40% CF (High-CM); 30% CM + 70% CF (Low-CM); 60% poultry manure (PM) + 40% CF (High-PM), and 30% PM + 70% CF (Low-PM). We used high-throughput sequencing of 16S ribosomal RNA gene amplicons to characterize the soil bacterial communities. Results revealed that the addition of manure significantly altered the soil bacterial community composition and structure; and enhanced the relative abundance of phyla Proteobacteria, Chloroflexi, Firmicutes, Acidobacteria, and Planctomycetes. Organic fertilizer treatments, particularly high CM and PM had the highest measured soil bacterial diversity of all treatments. Similarly, integrated application of manure and CFs increased the soil biochemical traits ( pH, total N [TN], soil organic C, microbial biomass N [MBN] and microbial biomass C [MBC]) and rice grain yield. Average increases in SOC, TN, MBN and MBC were 43.66%, 31.57%, 24.34% and 49.45%, respectively, over the years in the High-PM compared with Pos-Con. Redundancy analysis showed that the dominant bacteria phyla were correlated with soil pH, SOC, TN, and microbial biomass, but the relative abundance of Proteobacteria was strongly correlated with environmental factors such as soil pH, SOC, TN and MBC. We employed a structural equation model to examine the relationship between microbial biomass, soil nutrients and grain yield among treatments. Overall, the findings of this research suggest that the integrated application of CF and manure is a better approach for improving soil health and rice yield.